Gambaran Indikator Klinis Diagnosis Keperawatan Insomnia Menggunakan Insomnia Severity Index pada Pasien Hemodialisis - Ayu Dwi Silvia Putri; Totok Harjanto; Intansari Nurjannah (PSIK FKKMK UGM, 2017)
Background: End Stage Renal Disease is a condition of chronic kidney disease characterized by decreased renal function that requires hemodialysis therapy. Hemodialysis causes several effects, one of which is insomnia.Objective: To identify clinical indicator of nursing diagnosis for insomnia using Insomnia Severity Index (ISI) as the measuring instrument.Methods: This was descriptive research with cross-sectional design. Respondents in this study were patients undergoing hemodialysis which amounting in total to 72 patients. Two instruments, ISI and NANDA-I for Insomnia (an instrument developed from clinical indicators of nursing diagnosis), were used in this research. Then, the most appeared ISI’s clinical indicators at every level of insomnia were analyzed using univariate analysis.Results: The ISI’s clinical indicators which appear in all severe insomnia patients are: early awakening, difficulty in initiating sleep, difficulty in maintaining sleep, alteration in sleep pattern (sleep quantity and quality change), health status shifting, sleep disturbance with an impact on the next-day, exhausted, decreased quality of life, mood swing, and haggard. Only one ISI’s clinical indicator which appears in all moderate insomnia patients which is alteration in sleep pattern (sleep quality change). On the mild insomnia, there is not any clinical indicator which appear in every patient; however, patients are likely to experience alteration in sleep pattern (sleep quantity and quality change).Conclusions: Ten clinical indicators of insomnia nursing diagnosis found in patients with severe insomnia need to be considered as the main indicator in patients with insomniac nursing diagnosis. ABSTRAK Latar belakang: End Stage Renal Disease adalah penyakit ginjal kronis yang ditandai dengan menurunnya fungsi ginjal sehingga membutuhkan terapi hemodialisis. Hemodialisis menimbulkan beberapa dampak, salah satunya adalah insomnia.Tujuan: Mengetahui gambaran indikator klinis diagnosis keperawatan insomnia yang diukur menggunakan Insomnia Severity Index (ISI).Metode: Penelitian ini merupakan penelitian deskriptif dengan rancangan cross-sectional. Responden dalam penelitian ini adalah 72 pasien yang menjalani hemodialisis. Pengukuran insomnia pada responden dilakukan menggunakan dua instrumen yaitu ISI dan instrumen yang disusun dari indikator klinis diagnosis keperawatan insomnia berdasarkan NANDA-I. Peneliti menganalisis indikator klinis yang muncul pada setiap tingkatan insomnia berdasarkan ISI.Hasil: Indikator klinis yang terdapat pada insomnia berat sesuai ISI adalah: bangun terlalu dini, kesulitan memulai tidur, kesulitan mempertahankan tidur, gangguan pola tidur (perubahan kuantitas dan kualitas tidur), perubahan status kesehatan, gangguan tidur yang berdampak pada keesokan hari, tidak berenergi, penurunan kualitas hidup, perubahan suasana hati, dan tidur tidak memuaskan. Indikator klinis yang terdapat pada pasien dengan insomnia sedang sesuai ISI adalah gangguan pola tidur (perubahan kualitas tidur). Pada insomnia ringan, tidak ada indikator klinis yang muncul pada pasien, namun pasien cenderung mengalami gangguan pola tidur (perubahan kuantitas dan kualitas tidur).Kesimpulan: Sepuluh indikator klinis diagnosis keperawatan insomnia yang terdapat pada pasien dengan insomnia berat perlu dipertimbangkan sebagai indikator utama pada pasien dengan diagnosis keperawatan insomnia.